2012
DOI: 10.1371/journal.pone.0046990
|View full text |Cite
|
Sign up to set email alerts
|

miR-205 Expression Promotes Cell Proliferation and Migration of Human Cervical Cancer Cells

Abstract: MicroRNAs (miRNAs) are short non-coding RNA regulators that control gene expression mainly through post-transcriptional silencing. We previously identified miR-205 in a signature for human cervical cancer using a deep sequencing approach. In this study, we confirmed that miR-205 expression was frequently higher in human cervical cancer than their matched normal tissue samples. Functionally, we demonstrate that miR-205 promotes cell proliferation and migration in human cervical cancer cells. To further understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
97
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(107 citation statements)
references
References 60 publications
9
97
0
Order By: Relevance
“…These studies indicate that the dysregulation of miRNAs is frequently involved in carcinogenesis and cancer progression and, moreover, they suggest that the pathogenesis of cervical carcinoma may be attributed to miRNAs. In addition, miRNA expression profiling can also be used to predict the clinical outcome of cancer patients ( Jiang et al, 2008;Xie et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…These studies indicate that the dysregulation of miRNAs is frequently involved in carcinogenesis and cancer progression and, moreover, they suggest that the pathogenesis of cervical carcinoma may be attributed to miRNAs. In addition, miRNA expression profiling can also be used to predict the clinical outcome of cancer patients ( Jiang et al, 2008;Xie et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports from other labs and our lab have shown that many miRNAs are aberrantly expressed in cervical cancer and that miRNAs can act as tumor suppressors (e.g., miR-302-367, miR-424, miR-214) [9][10][11][12] or enhancers (e.g., miR-205, miR-21, miR-19a/b) [13][14][15]. Although some progress has been achieved in the past decades, much more effort is needed to elucidate the occurrence and mechanism of cervical cancer.…”
Section: Introductionmentioning
confidence: 61%
“…In recent years the prognostic value of microRNAs in cervical carcinoma was subjected (23). In cervical carcinogenesis, Xie et al were able to identify a regulatory influence of miR-205 (microRNA-205) triggering Cyr61 down-regulation in CC tissues (24). This is the first study to evaluate the expression and clinical impact of Cyr61 in CC.…”
Section: Discussionmentioning
confidence: 99%